ДЕМОКРАТИЯ – АДАМЗАТ РАЎАЖЛАНЫЎЫНЫҢ БАС ЖОЛЫ - Абаев, С.А.; Якубов, М.А. (FAN va JAMIYAT, 2016)
The article deals with the essence, content and different aspects of modern comprehension of the concept ―democracy‖. On the basis of the works of the first President of Uzbekistan Islam Karimov particular qualities of building the composition of democratic society in our country have been studied